2021
DOI: 10.3390/su131810188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Environmental Education on Ecologically Friendly Behavior of University Students in Pakistan: The Roles of Environmental Responsibility and Islamic Values

Abstract: With increasing global environmental problems, considerable evidence now suggests that environmental education can influence students’ ecologically friendly behavior significantly. Addressing increased environmental problems requires better understanding of the relations between focused and explicit environmental education, environmental responsibility, and religious values. The current study examined the relationship between environmental education and ecologically friendly behavior, utilizing insights from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…If the goal of environmental education is to increase knowledge and awareness of environmental issues and needs (Westover 2001), CLF has satisfied this intent. In addition, our study supports a previous finding (Begum et al 2021) citing religious values as an influential factor in the formation of environmental behavior, thus also supporting the Catholic Church's advocacy in promoting environmental awareness in the country.…”
Section: Discussionsupporting
confidence: 89%
“…If the goal of environmental education is to increase knowledge and awareness of environmental issues and needs (Westover 2001), CLF has satisfied this intent. In addition, our study supports a previous finding (Begum et al 2021) citing religious values as an influential factor in the formation of environmental behavior, thus also supporting the Catholic Church's advocacy in promoting environmental awareness in the country.…”
Section: Discussionsupporting
confidence: 89%
“…Moral and behavioral consciousness regulates different factors that are instrumental in decision making, which include the environment, existing culture, economic status, and intrinsic motivations [ 28 , 29 ]. Developing moral consciousness among people is instrumental in reviewing personal actions such as the consumption of fossil fuels, which is the largest source of environmental degradation and a major contributor to global warming [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moral education also extends to trade, as identified by Ha-Brookshire et al [ 59 ], who said that it helps to train current and future professionals so that they can build sustainable companies and supply chains that cut across the globe. Begum et al [ 31 ] noted that pro-environmental behavior is developed as a result of moral education. Further, moral education leads to a recognition of the common future of mankind, which leads to a global partnership [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a recent study proposed that the Malaysian government should integrate the element of religion into environmental policies, and major institutions such as education and media should use religion as an element to enhance EEB (Abdullah & Keshminder, 2020). Additionally, another recent study found that Islamic values positively moderated the relationships between environmental education and ecologically friendly behavior, as well as between environmental education and environmental responsibility (Begum et al, 2021). In comparison, the Muslim respondents in Malaysia were more influenced by the social factors than the religious factors.…”
Section: Discussionmentioning
confidence: 99%